Ijtihad Hukum Umar Bin Khattab Dalam Perspektif Hukum Islam - Ardiansyah, Fitra; Andhika Bayu Pranata; Dafa Syah Bahri; Miranda Einilia; Nurhalimah Putri Dongoran (Tabayyun : Journal Of Islamic Studies, 2024)
This article addresses new and contemporary problems and calls for improvements. It is important for religious advocates to understand that, depending on the circumstances and requirements, many legal questions have been resolved. Therefore, they had to research and re-evaluate thoroughly. This research category includes literary research. This study also found that there are five different periods in the history of the development of ijtihad: the time of Rasulullah SAW, the companions, the tabiin period (the time of the madhhab imams), the period after the madhhab imams, which has passed the period of taqlid and the decline of ijtihad, and now, or the contemporary period . Increasing the vitality of Islamic law is one of the latest and most up-to-date ways of applying ijtihad in addressing modern Islamic legal problems